TEST-SYSTEM BASED ON INDIRECT “SANDWICH” ELISA TO DETECT THE LUMPY SKIN DISEASE VIRUS ANTIGEN - O. A. Ryabikina; V. I. Diev; O. P. Byadovskaya; A. V. Konstantinov; S. K. Starov; A. V. Kononov; V. Yu. Kulakov; O. N. Petrova (Ветеринария сегодня)
Lumpy skin disease is an economically significant disease as it results in decrease in weight gain and milk yield, abortions, mastitis, reproduction disorders, animal emaciation, lesions of respiratory organs and in some cases – death. Today the disease is included in the OIE list and is subject to obligatory notification. The emergence and spread of the disease in the Russian Federation necessitated performance of tests in the framework of laboratory diagnosis method improvement. The test-system based on the indirect “Sandwich” ELISA for diagnosis of lumpy skin disease allowing performance of biomaterial tests within 24 hours was for the first time developed in Russia. The test-system development included antibody preparation in laboratory animals (rabbits and guinea pigs), selection of optimal dilution of capture and detection antibodies, composition of a buffer solution and conditions of the reaction procedure. 50 samples of initial culture antigens of the lumpy skin disease virus as well virus-containing suspensions collected on different stages of purification and concentration were tested using this technique. To confirm the ELISA results all analyzed samples were tested using RT-PCR. Besides, the virus infectivity titer was determined by titration in YaDK-04 (Goat gonad cells). The test specificity was 100%, and analytical sensitivity – 3.5 lg TCD50. The developed “Sandwich” ELISA allows performing tests of 24 antigen samples at 1:2–1:16 dilution simultaneously using 96-well plate and it can be used for lumpy skin disease diagnosis.